2007
DOI: 10.1063/1.2775804
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electromagnetic wave absorption properties of Fe nanowires in gigaherz range

Abstract: Fe nanowires with 70–200nm in diameter and 20–50μm in length were synthesized by a chemical vapor deposition method for electromagnetic wave absorption application. The frequency dependences of relative permittivity (εr) and permeability (μr) were strongly dependent on the diameter of Fe wires. Compared with micrometer wires or flakelike samples, nanowires exhibited a magnetic resonance (μr″) peak in the range of 1–18GHz, suggesting that nanowires have significant effect for reducing the eddy current loss, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
101
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 20 publications
3
101
0
Order By: Relevance
“…Moreover, the aforesaid result is more excellent than those reported in literature, i.e. Fe-Cr-Si-Al alloy flakes [11], Fe flakes [12,13], and Co nameplates [ 2 0]. The enhanced broadband absorption properties are attributed to the multi-resonance absorption and excellent electromagnetic properties of the flaked particles.…”
Section: The Microwave Absorbing Property Dependence On Liquid-solid supporting
confidence: 41%
See 1 more Smart Citation
“…Moreover, the aforesaid result is more excellent than those reported in literature, i.e. Fe-Cr-Si-Al alloy flakes [11], Fe flakes [12,13], and Co nameplates [ 2 0]. The enhanced broadband absorption properties are attributed to the multi-resonance absorption and excellent electromagnetic properties of the flaked particles.…”
Section: The Microwave Absorbing Property Dependence On Liquid-solid supporting
confidence: 41%
“…Wang et al [11] found that with the increase of the aspect ratio and size, the complex permittivity and permeability of Fe-Cr-Si-Al alloy flakes rose and the matching properties declined. At present, the literatures reported mainly focus on the alloy flakes and there is only a little literature about flaked iron [12,13]. Furthermore, the relationship between the microstructure and properties (e.g.…”
mentioning
confidence: 99%
“…FeCo composites, such as Y 2 O 3 /FeCo shell/core nanocomposites [8], Al 2 O 3 and C-coated FeCo nanocapsules [9,10], have been developed and an expected microwave absorption ability is obtained because of a better electromagnetic match. In addition, the microwave magnetic properties of the composites also depend on the morphology of magnetic materials [11,12]. Variety of microwave absorbers with different morphologies (Fe nanoparticles encapsulated in carbon nanotubes, Ni nanowires, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 shows the calculated theoretical RLs of the Bi 2 S 3 / paraffin nanocomposites with different loadings (10,20, and 40 wt %) and different thicknesses in the frequency range of 2-18 GHz. Since a paraffin matrix is transparent to microwaves, these results are generally regarded as the wave-absorption capacities of the filler itself (that is, Bi 2 S 3 in this study) for further comparison with other nanocomposites.…”
Section: Resultsmentioning
confidence: 99%